2002
DOI: 10.1001/archpedi.156.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Family Perspectives on the Quality of Pediatric Palliative Care

Abstract: There is a need to improve pediatric palliative care. Recurring themes in the family interviews suggest useful issues to consider in the development of a palliative care program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
343
1
51

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(411 citation statements)
references
References 21 publications
16
343
1
51
Order By: Relevance
“…[17][18][19][20] In our study, practitioners verbally dominated family meetings talking substantially more than actorfamily members (70 vs 30%). Our results using realistic enactments are strikingly consistent with the findings of McDonagh et al, 21 who reported that in actual end-of-life conferences in adult intensive care units (ICUs), clinicians spoke 71% and family members 29% of the time.…”
Section: Discussionmentioning
confidence: 52%
“…[17][18][19][20] In our study, practitioners verbally dominated family meetings talking substantially more than actorfamily members (70 vs 30%). Our results using realistic enactments are strikingly consistent with the findings of McDonagh et al, 21 who reported that in actual end-of-life conferences in adult intensive care units (ICUs), clinicians spoke 71% and family members 29% of the time.…”
Section: Discussionmentioning
confidence: 52%
“…Parents wanted to receive honest information about their infant's condition and prognosis, even if the news was not good, which is similar to previous research. 11,13,14,23 They wanted to be involved in decision-making for their infant, and wanted their decisions to be respected by medical staff. If parents felt involved in the decision-making for their infant, they appeared to have a more positive perception of their infant's end-of-life care, regardless of how long their infant lived.…”
Section: Discussionmentioning
confidence: 99%
“…10 These data suggest that palliative care consultation may enhance the end-of-life care for newborns, but there are still questions about what constitutes an excellent end-of-life care. Although several studies have asked the parents of children who have died about their perspectives on their child's end-of-life care, 11,12,13 these studies were not specific to parents who had lost an infant. One study that did ask parents who had an infant die in a neonatal intensive care unit 14 found that parents wanted clear information about their child's condition, and wanted to be involved in decisions that were made about their child's care.…”
Section: Introductionmentioning
confidence: 99%
“…5 professionals are recognized as determinants of providing high-quality paediatric palliative care [14][15][16] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%